Analysis of Students' Difficulty Factors in Learning English at SMP Negeri 23 Kabupaten Tebo - Rauldatul Husni; Annisa Ayunita (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the English language skills of students who experience difficulties in English, the factors that cause difficulties and how to overcome difficulties in learning English. The method used in this study is a qualitative description in which data collection is carried out by direct observation and communication techniques. Data collection tool using interviews and also observation. This research involved several teachers and students in a school. The results of this study state that the factors causing this difficulty occur from internal factors and external factors. Internal factors, such as the lack of student interest in learning in class. While external factors include teacher learning methods in class. Efforts that can be made to overcome this are by understanding student characteristics, types of student learning in class, developing student motivation and also evaluating each lesson